1994
DOI: 10.1097/00002727-199411000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the insignificant

Abstract: This was an inductive descriptive study of supportive behaviors and sources of supportive behaviors in 20 critically ill, adult, pretransplant liver patients. Data were collected using a demographic tool and a semistructured interview schedule focusing on sources of support and supportive behaviors. Demographic data were analyzed by using frequencies, and interview data were analyzed utilizing content analysis. Participants were 28 to 68 years of age and considered themselves to be supported and critically ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In general, the contribution of family support to patient recovery has been described as a part of the much broader social support system (Kupferschmid et al, 1991). Geary et al (1994) reported that ''someone with you'', e.g. a family presence with the patient, was one of the major themes developed from their interviews with 20 critically ill patients prior to liver transplant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the contribution of family support to patient recovery has been described as a part of the much broader social support system (Kupferschmid et al, 1991). Geary et al (1994) reported that ''someone with you'', e.g. a family presence with the patient, was one of the major themes developed from their interviews with 20 critically ill patients prior to liver transplant.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous researchers have conducted studies of the experiences of critically ill patients and the needs of their family members (Beach et al, 1992;Burr, 1996;Davies, 2000;Fridlund et al, 1993;Chien et al, 2006;Chui and Chan, 2007;Foster and Chaboyer, 2003;* Geary et al, 1994* Geary et al, , 1997Gortner et al, 1988;Holl, 1993;Johnson et al, 2001;Mishel and Murdaugh, 1987;Mutran et al, 1997;Parker, 1997;Saxe-Braithwaite and Chapman, 1992;Simpson, 1991). However, few have investigated the experiences and interactions that make up the informal support and care of both these groups of patients and their main family carers (MFC) simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Fear, anxiety, agony, self‐concept alterations including body image, self‐esteem and role performance disturbance, loneliness, depersonalization, along with perceived powerlessness, hopelessness, bewilderment and acute confusion, to terror attacks and panic are among the better documented psychosocial alterations in the critically ill (Grendell, 1998; Lusk and Lush 2005). A need to feel safe was identified as their primal need by ICU patients (Hupcey, 2000), whereas, the significance of emotional support by staff and family members has been emphasized (Geary et al , 1994, 1997).…”
Section: Review Of Background Literaturementioning
confidence: 99%
“…Although the surveillance team in many ways supported them in the waiting period, it also imposed special directions and limits to movement. Social support from family and friends was not a major theme in most studies but considered important when explicitly explored such as in Geary, Formella and Tringali's (1994) study.…”
Section: Introductionmentioning
confidence: 99%